Evaluasi Program Bulan Imunisasi Anak Nasional (BIAN) Di Dinas Kesehatan Kota Tasikmalaya - Eneng Iyet Kurniawati; Nanik Yuliwati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: The COVID-19 pandemic has resulted in an increasing number of children who have not had complete routine immunizations. Then efforts are needed for National Child Immunization Month (BIAN) activities. BIAN's goal is to achieve and maintain high and even population immunity as an effort to prevent PD3I outbreaks. The implementation of BIAN is carried out simultaneously in the City of Tasikmalaya. The BIAN coverage situation in Tasikmalaya City includes measles/rubella 96.2%, OPV 93.6%, IPV 89.3%, DPT-HB-Hib 93.2%. While the achievements at the Cipedes Health Center included MR 96%, OPV 100%, IPV 82%, and HIB DPT 83%. The purpose of this study was to obtain in-depth information regarding the Evaluation of the National Child Immunization Month Program (BIAN) at the Tasikmalaya City Health Office in 2022. Methods: This type of research is the Rapid Assessment Procedure (RAP). This research was conducted in the Tasikmalaya City Health Office area in March-June 2023. The informants in this study were as many as 10 people consisting of Immunization Program Holders (7 people) for each health center, and health service officers (3 people). Results: The input aspect in implementing BIAN at the Tasikmalaya City Health Office, includes personnel for implementing BIAN consisting of health workers and midwives called Korim (Immune Coordinator), insufficient funds, facilities and infrastructure to support the BIAN program including leaflets, banners and banners as well as technical guidelines and SOPs on the implementation of BIAN from technical guidelines provided by the government, as well as the timeframe for implementing BIAN for approximately 2 months. Process aspects in implementing the BIAN Program, consisting of sufficient vaccine availability, recording and reporting using the ASIK application. The output aspect in the Implementation of the BIAN Program consists of BIAN coverage which is already above 95% and the achievements of the BIAN that have been carried out have reached the target. The obstacles faced in the implementation of the BIAN Program are that most people, especially parents, are reluctant to immunize their children because they are afraid of the effects of the vaccine because there is a lot of confusing information from the environment which states that vaccines are not safe and actually add to the severity of the disease. Conclusion: All aspects of the implementation of BIAN are running smoothly even though there are still obstacles, especially from the community, so the service should always appeal to the heads of each puskesmas to provide counseling about the importance of immunization, especially during a pandemic and the puskesmas to assist cadres in the division of tasks for each cadre